2014
DOI: 10.1021/es5009467
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing Reveals Bacterial Communities in Unchlorinated Drinking Water Distribution System: An Integral Study of Bulk Water, Suspended Solids, Loose Deposits, and Pipe Wall Biofilm

Abstract: The current understanding of drinking water distribution system (DWDS) microbiology is limited to pipe wall biofilm and bulk water; the contributions of particle-associated bacteria (from suspended solids and loose deposits) have long been neglected. Analyzing the composition and correlation of bacterial communities from different phases helped us to locate where most of the bacteria are and understand the interactions among these phases. In the present study, the bacteria from four critical phases of an unchl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
171
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(189 citation statements)
references
References 69 publications
15
171
3
Order By: Relevance
“…Firmicutes has usually been found to be a minor component of DWDS bacterial communities in both in bulk waters (Kormas et al, 2010;Lu et al, 2013;Pinto et al, 2012;Vaz-Moreira et al, 2013), and biofilms (Lin et al, 2013;Liu et al, 2014;Revetta et al, 2013). Our previous study showed that Firmicutes was usually a rare species in pipe biofilms from a real urban DWDS, while in few cases it could be a major component of biofilm bacterial community (Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Firmicutes has usually been found to be a minor component of DWDS bacterial communities in both in bulk waters (Kormas et al, 2010;Lu et al, 2013;Pinto et al, 2012;Vaz-Moreira et al, 2013), and biofilms (Lin et al, 2013;Liu et al, 2014;Revetta et al, 2013). Our previous study showed that Firmicutes was usually a rare species in pipe biofilms from a real urban DWDS, while in few cases it could be a major component of biofilm bacterial community (Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the relative importance of different proteobacterial classes in DWDS biofilm bacterial community remained unresolved (Wu et al, 2015). Previous studies showed the dominance of either Alphaproteobacteria (Douterelo et al, 2013;Gomez-Alvarez et al, 2014;Krishna et al, 2013), or Betaproteobacteria (Lee et al, 2005;Liu et al, 2014;Sun et al, 2014), while both of them could be dominant Wu et al, 2015). Moreover, Gammaproteobacteria could also be the largest bacterial group in DWDS biofilms (Douterelo et al, 2013;Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The parameters that have been investigated in our study have been identified in all these three niches, but seem to differ in the preferred niche they occupy, with fungi being dominantly present in pipe wall biofilms, Aeromonas and HPCs in sediments and Mycobacterium spp., ATP and cell numbers in pipe wall biofilms and sediments. 15,24 Microbial growth in pipe wall biofilms, sediments and water will result in increased microbial numbers in drinking water and, therefore, regrowth indicators measured in drinking water should reflect growth in each of these three niches. In the past, ATP and cell counts have been proposed as alternative parameters for HPCs to determine microbial regrowth in drinking water distribution system.…”
Section: Discussionmentioning
confidence: 99%